EFFECTIVENESS OF THE PROBLEM BASED LEARNING (PBL) MODEL INTEGRATING STEAM ON SCIENCE LEARNING OUTCOMES - Winda Aqsalita; Siti Masfuah; M. Syafruddin Kuryanto (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
This problem stems from the low learning outcomes of grade V students in the IPAS subject. The purpose of this study was to improve IPAS learning outcomes. The research methodology used is quantitative. The population of this study were all fifth grade students of SD N Mlekang 1, totaling 15 students selected using the saturated sample technique. The type of research used is pre-experimental with a one group pretest-posttest design. Data collection techniques in the form of tests and observation sheets. Data analysis using the N-Gain Test. The results stated that there was an increase in IPAS learning outcomes using STEAM-integrated PBL. The application is effective in learning and gets a score of 0.7513 with a high category, so it can be concluded that using the Problem Based Learning (PBL) learning model integrated with STEAM is effective in improving IPAS learning outcomes. Keywords: Problem Based Learning (PBL), STEAM, Learning Outcomes, IPAS.